2017
DOI: 10.1186/s12967-017-1148-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia enhances arsenic-induced platelet and megakaryocyte activation

Abstract: ObjectiveLow to moderate inorganic arsenic (iAs) exposure is independently associated with cardiovascular disease (CVD), particularly for patients with diabetes mellitus (DM). The mechanism of increased CVD risk from iAs exposure in DM has not been adequately characterized. We evaluated whether increasing concentrations of glucose enhance the effects of iAs on platelet and megakaryocyte activity, key steps in atherothrombosis.MethodsHealthy donor whole blood was prepared in a standard fashion and incubated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…All work was performed using the manufacturers’ protocols and as previously published. 29 , 30 Transcripts were normalized to the housekeeping gene RNA18S5 and are reported as fold change over control. All primers were obtained from Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…All work was performed using the manufacturers’ protocols and as previously published. 29 , 30 Transcripts were normalized to the housekeeping gene RNA18S5 and are reported as fold change over control. All primers were obtained from Integrated DNA Technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Newman et al (2017) studied the effects of an environmental pollutant, inorganic arsenic, and hyperglycemia in an in vitro model with platelets and MKs. They found that platelet activation markers (P-selectin and monocyte–platelet aggregates or leukocyte–platelet aggregates) increased with low levels of arsenic and with higher glucose concentrations but also with the co-incubation of arsenic and higher glucose concentrations.…”
Section: Mks Platelets and Thrombosis Riskmentioning
confidence: 99%
“…These proteins then bind to their receptors on Kupffer cells for advanced glycation end products, triggering the production of IL-6, and causing hepatocytes to secrete TPO, which further leads to increased megakaryocyte proliferation and reticulated platelet production [ 54 , 55 ]. Another study reported that hyperglycemia can enhance sodium arsenite-induced megakaryocyte adhesion, platelet P-selectin expression, and leukocyte-platelet aggregation [ 56 ]. Megakaryocyte adhesion is often considered one of the markers of atherothrombosis risk [ 57 ].…”
Section: Platelets and Risk Factors Of Atherosclerosismentioning
confidence: 99%